2011
DOI: 10.1021/ar200011r
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine for Cancer: Lipid-Based Nanostructures for Drug Delivery and Monitoring

Abstract: Recent advances in nanotechnology, materials science, and biotechnology have led to innovations in the field of nanomedicine. Improvements in the diagnosis and treatment of cancer are urgently needed, and it may now be possible to achieve marked improvements in both of these areas using nanomedicine. Lipid-coated nanoparticles containing diagnostic or therapeutic agents have been developed and studied for biomedical applications and provide a nanomedicine strategy with great potential. Lipid nanoparticles have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 24 publications
0
84
0
1
Order By: Relevance
“…[7][8][9][10][11][12][13] The most common types of nanoparticles used for the detection of cancer were fluorescent, radioactive, or superparamagnetic core nanoparticles which were rendered biocompatible by encapsulation with polymers or phospholipids. 7,11,14,15 Similarly, chemotherapeutic drugs were added to the encapsulants with the expectation that more efficacious therapies, with reduced global toxicity, would result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] The most common types of nanoparticles used for the detection of cancer were fluorescent, radioactive, or superparamagnetic core nanoparticles which were rendered biocompatible by encapsulation with polymers or phospholipids. 7,11,14,15 Similarly, chemotherapeutic drugs were added to the encapsulants with the expectation that more efficacious therapies, with reduced global toxicity, would result.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The most common types of nanoparticles used for the detection of cancer were fluorescent, radioactive, or superparamagnetic core nanoparticles which were rendered biocompatible by encapsulation with polymers or phospholipids. 7,11,14,15 Similarly, chemotherapeutic drugs were added to the encapsulants with the expectation that more efficacious therapies, with reduced global toxicity, would result. [16][17][18] These two types of nanoparticles are typically targeted to primary and/or metastatic tumors either passively by the enhanced permeability and retention effect, which relies on the leaky vasculature often found in tumors, or through active targeting of specifically overexpressed or highly expressed membrane antigens on the tumor cells or neovasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles provide unique physical and optical properties to serve as building blocks for a wide-ranging applications in nanoelectronics, nanophotonics, nanodevices, and nanomedicine [1][2][3][4][5]. Particularly, nanoscale gold exhibits properties which are fundamentally different from other nanoparticles [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…NPs are widely used in tumor treatment (eg, nuclear imaging, tumor therapy) because of their enhanced permeability and retention effect and subsequent increased accumulation on the surface of tumors. [27][28][29][30] In this study, it was observed that the conjugated GRP78BP can direct micelles to tumor tissues, thus improving the accumulation efficacy in tumors. This novel construct can enlarge the impact of NPs in the diagnosis of solid tumors.…”
mentioning
confidence: 91%